2020
DOI: 10.1097/mcg.0000000000001432
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Injury in Patients With COVID-19

Abstract: Background: Coronavirus disease 2019 (COVID-19) has infected over 2 million people worldwide over the course of just several months. Various studies have highlighted that patients infected with COVID-19 may develop various degrees of liver injury. Here, we discuss the impact of underlying liver disease and manifestations of hepatic injury with COVID-19. We also review mechanisms of hepatic injury. Methods: We searched the database PubMed for all studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Simple hepatic steatosis and non‐alcoholic steatohepatitis may also need to be distinguished as pre‐existing inflammatory conditions could be important in the severity of Covid‐19. A recent meta‐analysis confirmed that liver injury was common in Covid‐19, reaching 25%, with a worsening clinical outcome 130 …”
Section: Gut Dysbiosis Linked To Risk Factors Of Severe Covid‐19mentioning
confidence: 99%
See 1 more Smart Citation
“…Simple hepatic steatosis and non‐alcoholic steatohepatitis may also need to be distinguished as pre‐existing inflammatory conditions could be important in the severity of Covid‐19. A recent meta‐analysis confirmed that liver injury was common in Covid‐19, reaching 25%, with a worsening clinical outcome 130 …”
Section: Gut Dysbiosis Linked To Risk Factors Of Severe Covid‐19mentioning
confidence: 99%
“…It also increases antimicrobial peptide expression and gut barrier integrity 139 . Increased expression of antimicrobial peptides by vitamin D in the respiratory tract protects the lungs from viral infections 130 . Vitamin D in combination with magnesium and vitamin B12 are able to reduce oxygen support and intensive care in Covid‐19 131 .…”
Section: Preventive and Therapeutic Implicationsmentioning
confidence: 99%
“…Gastrointestinal symptoms have been described to occur up to 15% (4), and were attributed to viral cell invasion mediated by Angiotensin-Converting Enzyme 2 (ACE2) receptors at the enterocyte level (5). Although not fully understood, the involvement of the liver with elevated levels of hepatic enzymes in blood biochemistry tests has also been described to occur in 14-53% of the cases (6)(7)(8)(9)(10). Possible mechanisms that may be associated with liver damage during COVID-19 are (1) an immune-mediated inflammation; (2) a direct cytotoxic effect caused by viral replication of hepatocytes; (3) a drug-induced liver injury, including self-prescribing medications and those used for the treatment of COVID-19, such as remdesivir, tocilizumab, chloroquine; and (4) reactivation of previously existing liver diseases (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…However, COVID-19 patients frequently show evidence of damage to other organs. Furthermore, those with pre-existing liver disease or newly occurred evidence of liver injury have an increased likelihood of a poor prognosis (5,6). A number of studies have suggested that liver disease is one of the most common comorbidities of COVID-19 patients and a number of patients infected with SARS-CoV-2 can develop different degrees of liver injury (7,8).…”
Section: Introductionmentioning
confidence: 99%